Nanowires New Insights - Maaz, Khan (IntechOpen, 2017)
One-dimensional nanostructures, such as nanowires, have drawn extensive research interests in the recent years. The smaller size brings unique properties to the nanowires due to the finite size effect (quantum confinement effects). The unique geometrical features of the nanowires bring their utilization in many practical applications in the recent advanced technology. This book provides an updated review on fabrication, properties, and applications of various nanowires. This book is aimed to provide solid foundation of nanowires to the students, scientists, and engineers working in the field of material science and condensed matter physics.